Variant syndromes of primary biliary cholangitis. (June 2018) - Schulz, Lisa; Sebode, Marcial; Weidemann, Sören A.; Lohse, Ansgar W.
Abstract: Patients with primary biliary cholangitis (PBC) can show biochemical, serological and/or histological features of autoimmune hepatitis (AIH). The term 'AIH-PBC overlap syndrome' has been used frequently for these cases and implies the coexistence of two separate diseases. However, the boundaries between 'classical' PBC, PBC with features of AIH and 'classical' AIH are difficult to define, and therefore the term 'variant syndrome' should be preferred. A variant syndrome must primarily be assumed in PBC patients showing pronounced hepatitic activity, either expressed by elevated transaminases and raised levels of serum IgG/gammaglobulins or more specifically by liver biopsy showing a modified hepatitis activity index (mHAI) score of >4/18. The presence of AIH-specific autoantibodies also supports the diagnosis of a variant syndrome. The diagnosis must not be missed because individually adapted immunosuppressive treatment, analogous to AIH therapy, appears to have an important beneficial impact on the prognosis and should therefore be offered to these patients.